Intercultural Communication Strategy for the Development of International Student Service Systems - Marieti Debyora Gardiana; Rino Ardhian Nugroho; Albert Muhammad Isrun Naini; Sulistiyo Joko Wahyudi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The number of international students is an indicator of tertiary performance assessment, so each tertiary institution tries to attract prospective students from abroad with various program offers and services provided. This research was conducted using a qualitative descriptive approach with in-depth interviews with international student services staff with the aim of knowing and analyzing their communication strategies as well as the intercultural communication competencies that international student services staff need to possess. The study results were analyzed referring to the Theory of Communication Accommodation and Theory of Intercultural Communication, which then mapped out the findings based on Byram's Intercultural Communication Competence model (attitudes, knowledge, connecting skills, discovery and interaction skills, and critical cultural awareness). Knowing the intercultural communication strategies needed to serve international students is expected to improve the quality of services provided.